Valutazione dei fattori che influenzano le prestazioni sportive in atleti junior di kayak - Rynkiewicz, M.; Rynkiewicz, T.; Zurek, P. (Medicina dello Sport, 2014)
Aim. The aim of this study was to identify factors that affect sports performance in kayaking. Methods. We examined condition- and coordination-related motor skills of 18 male kayakers (mean age: 16.2 years) and determined relationships between these motor skills and sports performance. We also attempted to define the typical level of motor skill fitness of Polish junior kayakers and to compare our findings to results reported by other authors. Following tests and assessments were performed: paddling for 2000 m and 1000 m in a kayak; determining the maximum power achieved during kayak ergometer paddling; determining the maximum oxygen consumption and power achieved during kayak ergometer paddling at an intensity corresponding to the ventilator threshold (VT); determining body composition; running for 1500 m on a track; and measuring the strength, endurance and power achieved during six-repetition series of bench press and bench pull. We also determined the levels of dynamic and static balance of the athletes. Results. We observed significant relationships between paddling speed and power achieved at VT intensity, the velocity of barbell movement during the bench press and bench pull, and the level of static balance. We also observed a strong correlation between maximum power achieved during kayak ergometer paddling and kayak paddling speed. Accordingly, kayakers should demonstrate a high level of power at VT intensity and maximum power during kayak ergometer paddling. They should also demonstrate a high velocity of barbell movement during the bench press and bench pull, as well as a high level of static balance. Conclusion. On the basis of these results, we determined the typical level of fitness of Polish junior kayakers. The body structures and capabilities of the kayakers we examined did not differ markedly from related data reported by other authors.